2018
DOI: 10.1111/bju.14192
|View full text |Cite
|
Sign up to set email alerts
|

Prospective analysis of hydrogel spacer for patients with prostate cancer undergoing radiotherapy

Abstract: Injection of HS resulted in a reduction of irradiated rectal dose volumes along with minimal GI toxicities, irrespective of prostate size.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
20
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 25 publications
4
20
0
Order By: Relevance
“…Previous work has shown no statistically significant variation in rectum dose with CTV volume ranging up to 100 cc, and is consistent with our findings [ 21 ].…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…Previous work has shown no statistically significant variation in rectum dose with CTV volume ranging up to 100 cc, and is consistent with our findings [ 21 ].…”
Section: Discussionsupporting
confidence: 94%
“…Following hydrogel placement, almost all regions of the prostate have increased separation from the rectum, with the greatest mean increase seen at the prostate apex and midgland (Table 3C ). Several publications have described a wide range of post-hydrogel perirectal separation ranging from 0.6 to over 2 cm, but to-date few have described in detail the optimal location to obtain this perirectal measurement, or Δ measurement, resulting from hydrogel placement [ 11 , 14 , 21 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…Creating a spacing between the prostate and rectum, the injection of a hydrogel rectal spacer into the anterior perirectal space is a novel approach permitting the administration of higher doses of radiation to the prostate while minimising rectal irradiation, and hence rectal toxicity 1. Its safety and efficacy have been evaluated in randomised phase III studies, with low rates of spacer-related complications reported in literature 2 3.…”
Section: Discussionmentioning
confidence: 99%
“…The use of hydrogel spacers in radiotherapy for prostate cancer has gained noticeable interest in recent years, allowing administration of higher radiation doses to the prostate while minimising rectal toxicity. Its safety and efficacy has been evaluated in several studies, with very rare spacer-related complications having been reported in literature 1. We present the case of a patient who developed a spacer-related periprostatic abscess.…”
Section: Introductionmentioning
confidence: 99%
“…In this issue of the BJUI , Chao et al. report their prospective single‐centre experience of using a rectal spacer device. This was not a randomized study, and there was no control arm to assist in quantifying the clinical impact of inserting a spacer; however, the patient population that was studied closely reflects that undergoing radical radiotherapy in most oncology departments worldwide.…”
mentioning
confidence: 99%